2007
DOI: 10.1007/s10534-006-9055-6
|View full text |Cite
|
Sign up to set email alerts
|

The structure and function of heavy metal transport P1B-ATPases

Abstract: P(1B)-type ATPases transport heavy metals (Cu+, Cu2+, Zn2+, Co2+, Cd2+, Pb2+) across membranes. Present in most organisms, they are key elements for metal homeostasis. P(1B)-type ATPases contain 6-8 transmembrane fragments carrying signature sequences in segments flanking the large ATP binding cytoplasmic loop. These sequences made possible the differentiation of at least four P(1B)-ATPase subgroups with distinct metal selectivity: P(1B-1): Cu+, P(1B-2): Zn2+, P(1B-3): Cu2+, P(1B-4): Co2+. Mutagenesis of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
402
0
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(421 citation statements)
references
References 95 publications
(145 reference statements)
5
402
0
14
Order By: Relevance
“…These results provided direct evidence of Cu transport mediated by OsHMA5 protein in yeast. Guerinot, 2006; Argüello et al, 2007;Burkhead et al, 2009). The functional characterization of OsHMA5 in this study showed that it transports Cu and is involved in the xylem loading of Cu at the both vegetative and reproductive growth stages (Figs.…”
Section: Transport Activity Of Oshma5 In Yeastmentioning
confidence: 67%
See 1 more Smart Citation
“…These results provided direct evidence of Cu transport mediated by OsHMA5 protein in yeast. Guerinot, 2006; Argüello et al, 2007;Burkhead et al, 2009). The functional characterization of OsHMA5 in this study showed that it transports Cu and is involved in the xylem loading of Cu at the both vegetative and reproductive growth stages (Figs.…”
Section: Transport Activity Of Oshma5 In Yeastmentioning
confidence: 67%
“…A number of different transporters, such as Cation Diffusion Facilitator, Natural resistance-associated macrophage protein, ATPBinding Cassette, Zinc-and Iron-regulated-like Protein, and P-type ATPase, have been reported to be involved in the uptake, translocation, distribution, and homeostasis of nutrients (Hall and Williams, 2003;Krämer et al, 2007;Palmer and Guerinot, 2009). Among them, heavy metal-transporting P-type ATPase (HMA), the P 1B subfamily of the P-type ATPase superfamily, has been implicated in heavy metal transport (Williams and Mills, 2005;Grotz and Guerinot, 2006;Argüello et al, 2007;Burkhead et al, 2009). There are eight and nine members of P 1B -ATPase in Arabidopsis thaliana and rice (Oryza sativa), respectively (Williams and Mills, 2005).…”
mentioning
confidence: 99%
“…Among these systems, transporters of the P-type ATPases family (Arguello et al, 2007;Kuhlbrandt, 2004) are usually involved. We have demonstrated here that expression of the Salmonella P-type ATPase CopA is induced by copper ions in a CueR-dependent manner (Figs 1 and 2) and that deletion of the copA gene affects copper tolerance under both aerobic and anaerobic conditions (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of characterized pumps fall into one of the following categories: efflux pumps involved in detoxification of monovalent metals (copper † and silver) or efflux pumps involved in detoxification of divalent metals (zinc, cadmium, and mercury). These two groups differ in the presence of unique amino acid sequences in their transmembrane domains, presumably contributing to substrate specificity (7,8). This notion is further supported by functional analysis of various P-type pumps harboring these amino acid motifs.…”
mentioning
confidence: 99%